After modernity Husserlian reflections on a philosophical tradition - Mensch, James R.
This book provides an important new answer to the much-discussed question of the nature and possibility of philosophy following the collapse of the modern foundationalist paradigm. Mensch offers an alternative based in phenomenology. Using Husserl's analysis of temporality to reinvigorate Aristotle's account of time, he shows how the passing of modernity is actually an opening for doing metaphysics in a new nonfoundationalist manner. Positioning Husserl within a wider context, Mensch views him both as a culmination of the modern foundationalist paradigm and as providing a way to overcome it through his descriptive analyses.